Barbarians and savages in European travelogues to Africa (from 1687 till 1832) - (:unkn) unknown (My University, 2020)
This article is concerned with the lexical investigation of some twenty travel diaries in Western Africa written by European authors between the end of the seventeenth century with Cavazzi until the first quarter of the nineteenth century with geographer Douville. The article highlights the frequent use of the words barbarian and savage, and other related words, their interconnexions, the evolution of their usage and their relative synonymy. Their extension is also examined and the context in which they are used is compared to the semantic figures which emerge out of the entries “BARBARE” and “SAUVAGE” in contemporary dictionaries and encyclopedia.
Keywords: African Research